2023
DOI: 10.1021/acsami.2c23248
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating Uniform TiO2–CeO2 Solid Solution Supported Pd Catalysts by an In Situ Capture Strategy for Low-Temperature CO Oxidation

Abstract: Support properties regulation has been a feasible method for the improvement of noble metal catalytic performance. For Pd-based catalysts, TiO2–CeO2 material has been widely used as an important support. However, due to the considerable discrepancy in the solubility product constant between titanium and cerium hydroxides, it is still challenging to synthesize a uniform TiO2–CeO2 solid solution in the catalysts. Herein, an in situ capture strategy was constructed to fabricate a uniform TiO2–CeO2 solid solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…According to the previous literature, the peaks assigned to Ce 4+ are labeled as u‴ (916.9 eV), v‴ (898.4 eV), u (901.1 eV), v (882.6 eV), u″ (907.5 eV), and v″ (888.9 eV), while the peaks u′ (902.6 eV), u 0 (899.4 eV), v′ (884.4 eV), and v 0 (881.1 eV) are assigned to Ce 3+ . Generally, the concentration of Ce 3+ is correlated to the surface oxygen vacancies. As listed in Table , the surface ratio of Ce 3+ in Pt/CeO 2 -r (21.0%) is higher than in Pt/CeO 2 -o (13.8%), indicating that more intrinsic defect sites and oxygen vacancies on the surface of Pt/CeO 2 -r. Figure S4 shows normalized Raman spectra of CeO 2 and Pt/CeO 2 . The most intense peak at 461 cm –1 corresponds to the first-order F 2g symmetry of CeO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the previous literature, the peaks assigned to Ce 4+ are labeled as u‴ (916.9 eV), v‴ (898.4 eV), u (901.1 eV), v (882.6 eV), u″ (907.5 eV), and v″ (888.9 eV), while the peaks u′ (902.6 eV), u 0 (899.4 eV), v′ (884.4 eV), and v 0 (881.1 eV) are assigned to Ce 3+ . Generally, the concentration of Ce 3+ is correlated to the surface oxygen vacancies. As listed in Table , the surface ratio of Ce 3+ in Pt/CeO 2 -r (21.0%) is higher than in Pt/CeO 2 -o (13.8%), indicating that more intrinsic defect sites and oxygen vacancies on the surface of Pt/CeO 2 -r. Figure S4 shows normalized Raman spectra of CeO 2 and Pt/CeO 2 . The most intense peak at 461 cm –1 corresponds to the first-order F 2g symmetry of CeO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The most intense peak at 461 cm −1 corresponds to the first-order F 2g symmetry of CeO 2 . 51 The weak peak at 598 cm −1 is attributed to the defect-induced vibration mode (D). 15,31 Compared with Pt/CeO 2 -o, Pt/CeO 2 -r has a more prominent peak at 598 cm −1 , indicating a higher oxygen vacancy in Pt/CeO 2 -r, which is consistent with the XPS data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the introduction of metal atoms into CeO 2 crystals to construct composite oxides, such as TiO 2 –CeO 2 composite oxide, could further improve the reducibility as well as lattice oxygen mobility of CeO 2 , therefore boosting the catalytic performance of supported Pd catalysts in redox reactions. 105 In addition, the bimetallic catalysts typically exhibit better properties when compared with the constituent individual metals due to the optimized geometric and electronic properties of active sites caused by the synergistic effects in bimetallic catalysts. Wang et al 106 prepared the nanorod-shaped (Au–Pd)/CeO 2 catalysts which possess the interspersed nanorod structure with nanopores distributed among them.…”
Section: Application Of Cerium-based Oxide Catalysts To Catalytic Eli...mentioning
confidence: 99%
“…However, the exploration of a Pd catalyst supported by TiO 2 nanoparticles in Suzuki reactions is limited in the current literature. Despite the numerous advantages it offers, including heightened catalytic activity, tailored reactivity, improved selectivity, as well as enhanced stability, durability, and recyclability, this approach remains relatively under explored 22 , 30 . Researchers has demonstrated that TiO 2 significantly enhances catalyst performance, affording the ability to modulate catalytic activities for diverse reactions, spanning dehydrogenation 31 , hydrodesulphurization 32 , water gas shift 33 , and thermal catalytic decomposition 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%